Membrane-spanning lipids for an uncompromised monitoring of membrane fusion and intermembrane lipid transfer - Schwarzmann, Günter (J Lipid Res, 2015)
A Förster resonance energy transfer-based fusion and transfer assay was developed to study, in model membranes, protein-mediated membrane fusion and intermembrane lipid transfer of fluorescent sphingolipid analogs. For this assay, it became necessary to apply labeled reporter molecules that are resistant to spontaneous as well as protein-mediated intermembrane transfer. The novelty of this assay is the use of nonextractable fluorescent membrane-spanning bipolar lipids. Starting from the tetraether lipid caldarchaeol, we synthesized fluorescent analogs with fluorophores at both polar ends. In addition, we synthesized radioactive glycosylated caldarchaeols. These labeled lipids were shown to stretch through bilayer membranes rather than to loop within a single lipid layer of liposomes. More important, the membrane-spanning lipids (MSLs) in contrast to phosphoglycerides proved to be nonextractable by proteins. We could show that the GM2 activator protein (GM2AP) is promiscuous with respect to glycero- and sphingolipid transfer. Saposin (Sap) B also transferred sphingolipids albeit with kinetics different from GM2AP. In addition, we could unambiguously show that the recombinant activator protein Sap C x His(6) induced membrane fusion rather than intermembrane lipid transfer. These findings showed that these novel MSLs, in contrast with fluorescent phosphoglycerolipids, are well suited for an uncompromised monitoring of membrane fusion and intermembrane lipid transfer.